2006
DOI: 10.1038/ncb1491
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic signalling and the p16INK4a–Rb pathway cooperate to enforce irreversible cellular senescence

Abstract: The p16(INK4a) cyclin-dependent kinase inhibitor has a key role in establishing stable G1 cell-cycle arrest through activating the retinoblastoma (Rb) tumour suppressor protein pRb in cellular senescence. Here, we show that the p16(INK4a) /Rb-pathway also cooperates with mitogenic signals to induce elevated intracellular levels of reactive oxygen species (ROS), thereby activating protein kinase Cdelta (PKCdelta) in human senescent cells. Importantly, once activated by ROS, PKCdelta promotes further generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
381
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 457 publications
(398 citation statements)
references
References 30 publications
13
381
1
3
Order By: Relevance
“…In the present study, we have found that overexpression of RAC3 nuclear receptor co-activator protects cells from apoptosis induced by H 2 O 2 . In view of recent evidence that oxidative damage (that is ROS production) can serve a tumor-suppressor function (Takahashi et al, 2006), these findings raise the possibility that deregulation of the RAC3 nuclear receptor can promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, we have found that overexpression of RAC3 nuclear receptor co-activator protects cells from apoptosis induced by H 2 O 2 . In view of recent evidence that oxidative damage (that is ROS production) can serve a tumor-suppressor function (Takahashi et al, 2006), these findings raise the possibility that deregulation of the RAC3 nuclear receptor can promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 88%
“…While pharmacological interventions reducing ROS generation have been proven to be beneficial, it is unclear whether mitochondria are required for senescence. ROS derived from non‐mitochondrial sources (Takahashi et al , 2006) and imbalances in antioxidant defence (Blander et al , 2003) have equally been implicated in the process. Chemical and genetic interventions impacting on the mitochondrial electron transport chain have been shown to enhance OIS (Moiseeva et al , 2009); however, to date, no study has effectively evaluated the necessity of mitochondria for the induction of the senescent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…ROS have been shown to play important roles in senescence by inducing genomic damage (Parrinello et al , 2003), accelerating telomere shortening (von Zglinicki, 2002) and acting as drivers of signalling networks important for the maintenance of the senescent phenotype (Passos et al , 2010). However, other reports have also highlighted the importance of non‐mitochondrial ROS sources (Takahashi et al , 2006), redox stress (Kaplon et al , 2013) or deficits in antioxidant defence (Blander et al , 2003) in the development of senescence. Therefore, it remains unknown whether mitochondria are truly necessary for senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Premature senescence can be triggered by many stimuli, including oncogene imbalance. Like replicative senescence, oncogene-induced premature senescence is identified by senescence biomarkers such as senescenceassociated b-galactosidase (SA-b-gal) (Dimri et al, 1995), and is accompanied by increased expression of negative growth regulators including p53, p21 WAF1 and p16 INK4A (Bandyopadhyay et al, 2001;Bennett, 2003;Ohtani et al, 2004;Takahashi et al, 2006;Haferkamp et al, 2008). Several recent studies have shown that oncogene-induced premature senescence indeed occurs in premalignant human tumors and provides an initial barrier to tumor genesis in vivo (Hornsby, 2007;Acosta et al, 2008;Ansieau et al, 2008).…”
Section: Introductionmentioning
confidence: 99%